In Vivo Assessment of the Calcium Salt-Forming Ability of a New Calcium Silicate-Based Intracanal Medicament: Bio-C Temp - Naoki Edanami; Razi Saifullah Ibn Belal; Shoji Takenaka; Kunihiko Yoshiba; Rosa Edith Baldeon Gutierrez; Shintaro Takahara; Nagako Yoshiba; Naoto Ohkura; Yuichiro Noiri (MDPI AG, 2023)
Calcium salt precipitation induced by intracanal medicaments contributes to the formation of apical hard tissue during apexification. This study compared the calcium salt-forming ability of a new calcium silicate-based intracanal medicament (Bio-C Temp) with that of two commercial calcium hydroxide pastes (Calcipex Plane II and Vitapex) in a rat subcutaneous implantation model. Polytetrafluoroethylene tubes containing each of the three materials were subcutaneously implanted in 4-week-old male Wistar rats. After 28 days, the composition and amount of calcium salts formed at the material-tissue interface were assessed using micro-Raman spectroscopy, X-ray diffraction, and elemental mapping. The tested materials produced white precipitates that had Raman spectra with peaks corresponding to hydroxyapatite and calcite. X-ray diffraction detected hydroxyapatite formation on Calcipex Plane II and Vitapex implants, as well as calcite formation on all three materials. Elemental mapping revealed that Bio-C Temp generated significantly smaller calcium- and phosphorus-rich calcified regions within the subcutaneous connective tissue than Vitapex. These results indicate that Bio-C Temp produced less calcium salt in rat subcutaneous tissue than Vitapex, although all materials formed hydroxyapatite and calcite in rat subcutaneous tissue. Bio-C Temp could be less effective than Vitapex in promoting apical hard tissue formation during apexification.